The Role of C-Reactive Protein in the Early Prediction of Serious Pancreatic Fistula Development after Pancreaticoduodenectomy. (28th January 2018) - Malya, Fatma Umit; Hasbahceci, Mustafa; Tasci, Yunus; Kadioglu, Huseyin; Guzel, Mehmet; Karatepe, Oguzhan; Dolay, Kemal
Abstract : Introduction . Despite recent advances in surgical techniques, pancreatic fistulas are common. We aimed to determine the role of C-reactive protein in the prediction of clinically relevant fistula development. Materials and Methods . Data from patients who underwent pancreaticoduodenectomy between 2012 and 2015 is collected. Postoperative 1st, 3rd, and 5th day (POD1, POD3, and POD5) C-reactive protein (CRP) levels, postoperative pancreatic fistula (POPF) development, other complications, length of hospital stay, and mortality were recorded. Results . Of 117 patients, 43 patients (36.8%) developed complications (including fistulas). Of the patients developing fistulas, 21 (17.9%) had POPF A, 2 (1.7%) had POPF B, and 7 (6.0%) had POPF C. POD5 CRP and POD3 CRP were shown to be significantly correlated with mortality and development of clinically relevant POPF (p = 0.001 and p = 0.0001, resp.) and with mortality (p = 0.017 ), respectively. The development of clinically relevant POPFs (B and C) could be predicted with 90% sensitivity and 82.2% specificity by POD5 CRP cut-off level of 19 mg/dL and with 100% sensitivity and 63.6% specificity by the difference between POD5 and POD1 CRP cut-off level of >2.5 mg/dL. Conclusion . CRP levels can effectively predict the development of clinically relevant pancreatic fistulas.